Chemical composition and in situ ruminal disappearance of sorghum silages grown in the mexican humid tropic - Sergio RamÃrez OrdoÃ±es (Revista de la Facultad de Ciencias Agrarias, 2019)
The purpose was to evaluate the chemical composition and in situ ruminal dry matter disappearance of four types of grain sorghum silages, one brown midrib sorghum (bmr) and, a corn silage, grown under rainfed conditions in a humid tropical region of Mexico. The crops were established at three sites. At harvest, three minisilos per treatment were filled with forage previously chopped. Minisilos opened at 55 days and samples of silage taken to dry and ground to 1 mm to determine the chemical composition and in situ ruminal dry matter disappearance. The crude protein was higher (p<0.05) in sorghum silages than corn silage. In sorghum silages, bmr sorghum had the lowest (p0.05) in ADF and ADL to corn silage. The degradation parameters (a, b, c ) was higher (p0.05) in bmr sorghum and corn silages. In the humid tropics, bmr sorghum silages are a good alternative to corn silage, especially in the dry season.